(untitled) (Baghdad Science Journal, 2023)
Based on the diazotization-coupling reaction, a new, simple, and sensitive spectrophotometric method for determining of a trace amount of (BPF) is presented in this paper. Diazotized metoclopramide reagent react with bisphenol F produces an orange azo-compound with a maximum absorbance at 461 nm in alkaline solution. The experimental parameters were optimized such as type of alkaline medium, concentration of NaOH, diazotized metoclopramide amount, order additions, reaction time, temperature, and effect of organic solvents to achieve the optimal performance for the proposed method. The absorbance increased linearly with increasing bisphenol F concentration in the range of 0.5-10 μg mL-1 under ideal conditions, with a correlation coefficient of 0.9931 and a detection limit of 0.15 μg mL-1. The effect of different temperatures and different extraction time was studied on the leaching out and the data indicates that as time and temperature rising, the concentration of BPF leached out of all thermal papers increased. To confirm that extracts from thermal papers contained BPF, samples containing the analytic were subjected to high-performance liquid chromatography (HPLC-UV detector) analysis. The analysis was carried out on a C18 column with a mobile phase of acetonitrile/water (55/45v:v), and the detection was conducted spectrophotometrically at 230 nm. The retention time of standard BPF was determined to be 5.649 min and the peak eluting time for most thermal papers extract was at 5.6 minutes, demonstrating that BPF was present in the thermal papers. The method was applied to quantify the proposed analyses in a variety of samples with excellent results.